Goustave Courbet, 1819-1877 : the last of the romantics - Masanes, Fabrice (Taschen, 2006)
Unsentimental realism "I maintain," stated Gustave Courbet (1819-1877), "that painting is clearly a concrete art whose existence lies only in the representation of real and existing objects...." Courbet, who influenced and advised the fledgling Impressionists, was an outstanding representative of a naturalistic realism that highlights the contradictions and inequities in society. Revolutionary were Courbet`s style, with dark hues and heavy brushstrokes, and choice of subject--depictions the life of plain people treated in an unsentimental, down to earth manner. His influence was enormous during his lifetime; he was offered the cross of the Legion of Honor in 1872 but he refused it. A man always at odds with authority, be it artistic or political, Courbet became a member of the Paris Commune and was briefly imprisoned and forced to flee to Switzerland for the final years of his life.